Etiopatogênia da artrite-encefalite caprina e estratégias para seu controle - Lima, Érica Custódio de [UNESP] (2009)
The arthritis-encephalitis caprine vírus is found at mostly areas of the world, especially at the countries that milk goats is strongly tecnific, and already was found in many brasilian states. The illness causes greats econimics prejudice, influencing badly the productive life time of the flock, related with the low production, decrease of the reproductive performance and lost of the genetic potential, determining constants flock’s renew. Many authors calls the atention for the probable dissemination of the illness and reinforce the necessity of the adoption strong sanitary politics for the illnes control. The controls programs, basically, based on knowledeg of the target-cells, that keep and distribute the virus on the guests organisms; on the transmition way; on sensibility and specificity of the sorologics tests, as well as your frequency of realitation in the flock; and after all on the management that the flock is submeted